1957
DOI: 10.1111/j.1365-2621.1957.tb17501.x
|View full text |Cite
|
Sign up to set email alerts
|

IDENTIFICATION OF THE VOLATILE SULFUR COMPONENTS OF COOKED CABBAGE AND THE NATURE OF THE PRECURSORS IN THE FRESH VEGETABLEa

Abstract: It is well known that cabbage contains thermolabile sulfur compounds which evolve sulfurous odors. Simpson and Halliday (22) investigated the volatile sulfur produced by boiling cabbage during the period of cooking. The formation of hydrogen sulfide was attributed to the hydrolysis of allyl isothiocyanate, the mustard oil of the thioglucoside sinigrin. Masters and Garbutt (16) similarly described the volatile sulfur as sulfide sulfur, but made no identification of the volatile organic sulfur.The present inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

1961
1961
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 16 publications
1
24
0
1
Order By: Relevance
“…Similarly, exposure to methyl mercaptan did not affect the result of the H 2 S analysis. This result is consistent with the observations of Dateo et al [23], who described the selective reaction of lead acetate with H 2 S in the presence of mercaptans and absence of moisture. No interference from similar concentrations of SO 2 and mercaptans was observed for silver nitrate tubes, in agreement with previous findings using silver nitrate paper strips [17] and membranes [16].…”
Section: Methods Optimisationsupporting
confidence: 94%
See 1 more Smart Citation
“…Similarly, exposure to methyl mercaptan did not affect the result of the H 2 S analysis. This result is consistent with the observations of Dateo et al [23], who described the selective reaction of lead acetate with H 2 S in the presence of mercaptans and absence of moisture. No interference from similar concentrations of SO 2 and mercaptans was observed for silver nitrate tubes, in agreement with previous findings using silver nitrate paper strips [17] and membranes [16].…”
Section: Methods Optimisationsupporting
confidence: 94%
“…However, in the presence of high concentration of other sulfur containing compounds, interferences can be observed [23], resulting in erroneous readings. In fermentation, yeast metabolisms results in the accumulation of namely SO 2 , sulfides, and mercaptans.…”
Section: Methods Optimisationmentioning
confidence: 98%
“…It was well known that the major volatile sulphur component of cooked cabbage is derived from l ‐S‐methylcystein sulphide, a free amino acid occurring in cabbage. It was reported that l ‐S‐methylcysterine sulfoxide was more readily degraded to form dimethyl disulphide in cooked cabbage (Dateo et al. , 1997).…”
Section: Resultsmentioning
confidence: 99%
“…Components were identified by analysis of the fragmentation patterns in accordance with established direct-method techniques (Dunning, 1955;Rock, 1951).…”
Section: Distillatio~zmentioning
confidence: 99%